1961
DOI: 10.1084/jem.114.6.921
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Red Cell Sequestration by Cortisone

Abstract: The effect of cortisone on the sequestration of (a) antibody-coated red cells and (b) incubated red cells was studied in rats. Cortisone administration inhibited the hepatic sequestration of red cells altered by non-immune as well as by immune injury. There was a latent period of 2 days between the institution of cortisone therapy and its first manifest effect on hepatic sequestration. The splenic sequestration of altered red cells was not inhibited by cortisone, and there was no inhibition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Kaplan and Jandl (13) examined the clearance of antibody-coated cells in rats utilizing antisera prepared in rabbits and exposing the sensitized cells to fresh rat serum as 40% suspension prior to injection. They found that cortisone acetate therapy decreased sequestration of cells at all levels of sensitization studied.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan and Jandl (13) examined the clearance of antibody-coated cells in rats utilizing antisera prepared in rabbits and exposing the sensitized cells to fresh rat serum as 40% suspension prior to injection. They found that cortisone acetate therapy decreased sequestration of cells at all levels of sensitization studied.…”
Section: Discussionmentioning
confidence: 99%
“…The clearance rate of heat-damaged RBC from circulation was measured according to the method of Kaplan and Jandl [8]. The labeled RBC was heated for 40 min at 45 °C, thereafter 0.5 ml of 5,Cr-labeled RBC suspension was transfused into a rat via a tail vein.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that corticosteroids decrease the clearance of antibody-coated red cells in man (3,6) and rats (7) and IgG-and/or C3-coated red cells in guinea pigs (8). In the latter study Atkinson et al demonstrated that IgG-sensitized erythrocytes were cleared in corticosteroid-treated guinea pigs as if they had fewer IgG molecules per red cell, suggesting a decreased recognition of immunoglobulin-or complement-coated cells by the macrophages of the reticuloendothelial system of the steroid-treated animal.…”
mentioning
confidence: 94%